ANALISIS DATA TERKAIT TATA LETAK PABRIK DAN MATERIAL HANDLING SERTA USULANNYA (STUDI KASUS : PT. XXY) - Aris Fiatno; Anggara Hadi Syaputra; Irfan Alfajri (Jurnal Teknik Industri Terintegrasi, 2020)
This research was conducted in November to December 2019 at PT. Sejahtera Mandiri St. Raya Pekanbaru Bangkinang Km 16, Riau Province. This research aims to find out the layout of plant facilities and Material Handling of activities input until it becomes ouput. This activity is carried out by collecting data throug observation, interviews, to take several documents such as photographs. With these data are analyzed in terms of the layot of plant facilities and Material Handling at PT. Sejahtera Mandiri so it produces some proposed designs or proposed opinions related to the layout of plant facilities and Material Handling. The result of this study indicate that the layout of factory facilities and Material Handling PT Sejahtera Mandiri has been optimized according to factory area considerations but there are some input points, such as the allocation of several work stations and realted proposals Material Handling of one work station and other work station that aim can minimize production costs and production time.